Importance of agriculture in the face of climate change: department of la Libertad - Peru - Macines-Romero, Rogelio N. (2024)
The members of the Intergovernmental Panel on Climate Change have issued various reports on the possible impacts of climate change, and they also point out the need to mitigate its causes and adapt to new scenarios. The impacts will be diverse worldwide, with agriculture being one of the elements responsible, and it will also suffer the effects that in some cases will benefit some crops, but mostly the yield of crops will be negatively affected. Extreme events such as the El Niño phenomenon will occur more and more frequently, causing losses in the agricultural sector, putting at risk the supply of food produced in the northern part of Peru. Since 1977, the Multisectoral Commission for the National Study of the El Niño Phenomenon (ENFEN) was established in Peru, one of its objectives being to reduce the damage caused to the economy and population. In the department of La Libertad, rice and sugar cane are mainly produced, and there is also a high-altitude area where potatoes are produced, these products are destined for the internal food supply. Also thanks to agricultural exports, it is a major producer of asparagus, avocados and blueberries.